2010
DOI: 10.1007/s00425-010-1274-y
|View full text |Cite
|
Sign up to set email alerts
|

DBB1a, involved in gibberellin homeostasis, functions as a negative regulator of blue light-mediated hypocotyl elongation in Arabidopsis

Abstract: Double B-box 1a (DBB1a) belongs to the zinc-finger family proteins in Arabidopsis thaliana. Transcriptional analysis uncovered that the DBB1a gene expression was blue light-dependently regulated, and the transcript level of DBB1a in cry1cry2 was decreased but not in phyAphyB compared to wild type under blue light conditions. Transgenic plants containing pDBB1a:GUS (β-glucuronidase) displayed GUS activity in the vascular system of leaves and petioles. Green fluorescent protein (GFP)-fused DDB1a (DBB1a-GFP) prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 44 publications
0
53
0
Order By: Relevance
“…Light fluence-response analyses of BBX18 gain-and-loss-of-function lines proved that this gene is involved in blue light-dependent hypocotyl elongation as a negative regulator, and its phenotype is related to gibberellin signaling pathways. 65 Further experiments have proved that BBX18 is involved as a negative regulator of basal and acquired thermotolerance. 66 In addition, BBX18 has been related to flower development.…”
Section: Bbx Protein Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Light fluence-response analyses of BBX18 gain-and-loss-of-function lines proved that this gene is involved in blue light-dependent hypocotyl elongation as a negative regulator, and its phenotype is related to gibberellin signaling pathways. 65 Further experiments have proved that BBX18 is involved as a negative regulator of basal and acquired thermotolerance. 66 In addition, BBX18 has been related to flower development.…”
Section: Bbx Protein Classificationmentioning
confidence: 99%
“…39 The expression of both transcripts is regulated by the circadian rhythm, and 35S:BBX18 and 35S:BBX19 overexpression plants display hyposensitivity to red and far-red light. Experiments by Wang and colleagues 65 demonstrated that BBX18 is a nuclear-localized protein. Light fluence-response analyses of BBX18 gain-and-loss-of-function lines proved that this gene is involved in blue light-dependent hypocotyl elongation as a negative regulator, and its phenotype is related to gibberellin signaling pathways.…”
Section: Bbx Protein Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] AtBBX18/DBB1a is involved in gibberellin homeostasis and the regulation of hypocotyl elongation in response to blue light. 16) Interestingly, AtBBX21/ STH2 and AtBBX22/STH3/LZF1 appear to be targets of COP1. 14,15) Based on knowledge from the seed plant A. thaliana, here we asked a fundamental question as to whether BBX-IV homologues are conserved in P. patens.…”
mentioning
confidence: 99%
“…AtBBX18/DBB1a is primarily responsive to blue light and AtBBX22/STH3/LZF1 to far-red light. 16,17) It is suggested, apart from regulatory mechanism, the property of light induction in PpBBX-IVg expression is conserved in P. patens. Here, another critical question is whether expression of them is subject to the diurnal oscillation in light and dark cycles, because it is known that most AtBBX-IV members, including AtBBX18 and AtBBX24, are under the control of the circadian clock.…”
mentioning
confidence: 99%